'The Pictures Which We Publish To-Day Are Fearful to Look Upon': The Circulation of Images of Atrocity During the American Civil War. Issue 1 (2nd January 2021) - Cross, Anne Strachan
Abstract : This article explores the circulation of photographs of prisoners of war that were taken at the US General Hospital in Annapolis, Maryland in 1864. More specifically, it considers the publication of these images as wood engravings in Harper's Weekly 's illustrated newspaper as part of a broader network of photographic circulation, and the circulation of images of atrocity during the American Civil War. This project follows recent interventions in photographic history that have emphasised reproduction and circulation, and that have decentred the photographic print as the primary site for the production of meaning. By examining the multiple visual and narrative contexts in which photographs of the Annapolis prisoners appeared, including as wood engravings in Harper's Weekly, this article reveals how divergent meanings were ascribed to the images, as both the press and the public sought to make sense of the prisoners' deterioration and to use their images for political purposes. Ultimately, the article employs circulation as a methodology to understand how audiences used photographs to make sense of the seemingly ineffable trauma and devastation of the American Civil War. This project also demonstrates how Harper's Weekly relied upon an existing public archive – of text and images, particularly cartes de visite – to report the news and to further its rhetorical position. It is important to highlight that the images in this article are disturbing. They show men in states of significant emaciation and were presumably taken without full consent. These pictures are shown as part of an effort to understand the ways in which images of atrocity were circulated in the nineteenth century, and, as such, requires that we consider the appropriateness of publishing and exhibiting such images both then and now. A question of care and of an ethics of looking must be at the forefront of this critical engagement.